Hareket'in İzleri: Nurettin Topçu'nun Erken Cumhuriyet Dönemiyle İlgili Eleştirel Görüşleri. - Yetim, Fahri (Mukaddime Journal)
Turkish intellectual life has followed a very dynamic course in the modernisation process with the power it has received from its ancient past. However, there are some deficiencies in theoretical approaches, analytical thinking and criticality in contemporary Turkish thought, which includes different theses about adaptation to the modernisation process. This situation, which is largely due to concerns about compensating for the historical delay, has led to a gradual narrowing of the environment of criticism over time. Hareket magazine, which is one of the steps towards the elimination of this deficit in the Republican period, is important for pioneering critical thinking at the philosophical level in the history of the Republic during its publication life, which started in 1939. Published with the initiatives of Nurettin Topçu, Turkey's first overseas doctoral associate professor of philosophy, Hareket magazine, which reached a large group of writers open to pluralism over time, made important contributions to the evaluation of the changes modern Turkey underwent from different perspectives with the critical texts it contained. In this respect, besides the evaluation of the journal Hareket as a whole, the articles written by Nurettin Topçu, who constitutes the main axis of the journal, especially in the early periods, contain a corpus that can bring alternative perspectives to Turkey's modernisation history. In this study, an evaluation will be made of some of the critical views in the journal Hareket, especially Topçu, within the framework of the approaches mentioned above, especially in the early Republican period, on the great change that Turkey has undergone with modernisation.